The Analysis of Strategic Management to Generating Graduates With Islamic Insight in Higher Education - Hasnadi Hasnadi; Rahmat Saputra (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
This article aims to describe and analyze the implementation of strategic management in generating graduates with Islamic. Data was collected through interviews, observation, document study, and Focus Group Discussion. Also, its analysis was performed by reducing, displaying and concluding data in accordance with the focus of the study. The results showed that the strategic management, which were conducted to produce graduate with competence in the field of nursing and have Islamic insight include, developing an Islamic vision and mission, compiling a curriculum based on Islamic insight, developing a Semester Lesson Plan (RPS) by incorporating Islamic values in an integrated manner in all courses, compiling Islamic activity programs in a strategic plan, carrying out activities in accordance with predetermined plans and schedules, conducting scheduled and continuous evaluations, as well as determining follow-up steps. Considering this result, all campus residents are required to behave in an Islamic manner, create an Islamic culture in the university environment, conduct Islamic studies regularly, and teach students skills in communication strategies, and motivation for patients through a religious approach.